PENGARUH STORE ATMOSPHERE, SOCIAL MEDIA PROMOTION, WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI HABBIT EATERY COFFEE MALANG - Mariana Puspa Dewi (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2021)
This research aims to find out and explain the effect of store atmosphere, promotion on social media and word of mouth on consumer purchasing decisions at the Habbit Eatery Coffee either partially or simultaneously. This research uses a quantitative approach. The sample of this study were 100 consumers of cafe omah root using non probability sampling method and accidental sampling technique. The instrument of this study uses a questionnaire and analyzed using multiple linear regression analysis. The results of this study indicate that store atmosphere partially has no effect on purchasing decisions, promotion on social media and word of mouth partially has a positive and significant effect on purchasing decisions. Simultaneously, store atmosphere, promotion on social media and word of mouth has a positive and significant effect on purchasing decisions.